Genomic alterations in breast cancer: level of evidence for actionability according to ESMO Scale for Clinical Actionability of molecular Targets (ESCAT). (31st January 2019) - Condorelli, R; Mosele, F; Verret, B; Bachelot, T; Bedard, P L; Cortes, J; Hyman, D M; Juric, D; Krop, I; Bieche, I; Saura, C; Sotiriou, C; et al.
Abstract: Better knowledge of the tumor genomic landscapes has helped to develop more effective targeted drugs. However, there is no tool to interpret targetability of genomic alterations assessed by next-generation sequencing in the context of clinical practice. Our aim is to rank the level of evidence of individual recurrent genomic alterations observed in breast cancer based on the ESMO Scale for Clinical Actionability of molecular Targets (ESCAT) in order to help the clinicians to prioritize treatment. Analyses of databases suggested that there are around 40 recurrent driver alterations in breast cancer. ERBB2 amplification, germline BRCA1/2 mutations, PIK3CA mutations were classified tier of evidence IA based on large randomized trials showing antitumor activity of targeted therapies in patients presenting the alterations. NTRK fusions and microsatellite instability ( MSI ) were ranked IC. ESR1 mutations and PTEN loss were ranked tier IIA, and ERBB2 mutations and AKT1 mutations tier IIB. Somatic BRCA 1/2 mutations, MDM2 amplifications and ERBB 3 mutations were ranked tier III. Seventeen genes were ranked tier IV based on preclinical evidence. Finally, FGFR1 and CCND1 were ranked tier X alterations because previous studies have shown lack of actionability.